ANALYSIS OF THE STATE OF BEEKEEPING IN SERBIA IN LINE SUSTAINABLE DEVELOPMENT IN AGRICULTURE - Nada MIJAJLOVIC; Jonel SUBIC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Serbia, beekeeping is one of the few agricultural branches with a positive export balance. Honey in Serbia is harvested from environmentally safe areas and certain types of honey are globally recognized and have a geographically protected origin, accordingly better quote on the global honey market and at are a more competitive price. Goal of this paper to analyze the state of beekeeping production in Serbia, to consider the legal frameworks and regulations in this field, investments and incentive measures implemented at the state level in order to improve this production. This paper will present the results of the analysis of parameters related to beekeeping production in the last ten years according to official statistics at the national level. Based on the analysis of the situation, it can be concluded that beekeeping has the potential to become a strategic economic sector. Interest in beekeeping in Serbia is in expansion and an increasing number of farms are officially registering this activity, following the regulations and world trends in this area, placing bee products on the market and earning significant revenues.